The impact of CYP2D6*41 on CYP2D6 enzyme activity using phenotyping methods in urine, plasma, and saliva - Jin, Ye; Zhang, Shuquan; Hu, Pei; Zheng, Xin; Guan, Xiaoduo; Chen, Rui; Zhang, Shuyang (Frontiers in Pharmacology, 2022)
Aims The CYP2D6*41 variant is the second or third frequent reduced function allele in Chinese with a frequency of around 3-4%, while it is the major reduced function allele in Indians, Saudi Arabians and Caucasians with frequencies of around 10-20%. The present study was designed to explore the impact of CYP2D6*41 on the metabolic activity of CYP2D6 using phenotyping methods in urine, plasma, and saliva. Methods We used dextromethorphan as the probe drug to analyze the phenotypes of 87 subjects with CYP2D6*1/*1 (n=22), CYP2D6*1/*2 (n=33), CYP2D6*2/*2 (n=4), CYP2D6*1/*41 (n=5), CYP2D6*2/*41 (n=3), CYP2D6*10/*41 (n=16), and CYP2D6*5/*41 (n=4) for CYP2D6. The ratio of parent drug to metabolite in 3 h saliva, 3 h plasma, and in 0-3h urine was considered the metabolic ratio. (MR). Results The CYP2D6*41 allele had substantial impact on the metabolic activity of CYP2D6 regardless of the urinary, plasma, or salivary phenotyping method used. In subjects with CYP2D6*1(or *2)/*1(or *2), *1 (or *2)/*41, *10/*41 and *5/*41 (all P < 0.001), the salivary, plasma, or urinary MR value increased. The MRs in saliva, plasma, and urine displayed high correlations. Conclusion The activity score system or the consensus activity score system, instead of the traditional phenotype classification, could predict the CYP2D6 enzyme activity more accurately. CYP2D6*41 had similar or more impact on the CYP2D6 enzyme activity as compared with CYP2D6*10. Assigning *41 a score of 0.5 and assigning *10 a score of 0.25 according to the consensus AS system should be reconsidered.